Using word clouds to present farmers' perceptions of advisory services on pollution mitigation measures - Vrain, E; Lovett, A (Taylor and Francis, 2019)
Advice delivery is one mechanism that can be used to encourage the uptake of water pollution mitigation measures amongst the farming community, but determining who is best placed to effectively provide advice and increase adoption creates a challenge for policy-makers. Through in-depth interviews, this research investigates the perspectives of both farmers and farm advisers on the delivery of water pollution mitigation advice in three agriculturally contrasting areas of England. A novel approach using word clouds as a visual comparative tool for qualitative data is presented to demonstrate a transferable method for disseminating research findings to a wider audience outside of academia. Results from the interviews indicate differences across the regions, and that contrasts exist between farmers and advisers' perceptions. This suggests it is important to assess both perspectives when designing effective advice delivery mechanisms and for policy-makers to consider who is most appropriate to effectively deliver farm advice.